Quantitative proteomics of Uukuniemi virus-host cell interactions reveals GBF1 as proviral host factor for phleboviruses - Uckeley, Zina Maria; Moeller, Rebecca; Kühn, Lars I.; Nilsson, Emma; Robens, Claudia; Lasswitz, Lisa; Lindqvist, Richard; Lenman, Annasara; Passos, Vania; Voss, Yannik; Sommerauer, Christian; Kampmann, Martin; et al. (Molecular & cellular proteomics, 2019)
Novel tick-borne phleboviruses in the Phenuiviridae family, which are highly pathogenic in humans and all closely related to Uukuniemi virus (UUKV), have recently emerged on different continents. How phleboviruses assemble, bud, and exit cells remains largely elusive. Here, we performed high-resolution, label-free mass spectrometry analysis of UUKV immunoprecipitated from cell lysates and identified 39 cellular partners interacting with the viral envelope glycoproteins. The importance of these host factors for UUKV infection was validated by silencing each host factor by RNA interference. This revealed Golgi-specific brefeldin A-resistance guanine nucleotide exchange factor 1 (GBF1), a guanine nucleotide exchange factor resident in the Golgi, as a critical host factor required for the UUKV life cycle. An inhibitor of GBF1, Golgicide A, confirmed the role of the cellular factor in UUKV infection. We could pinpoint the GBF1 requirement to UUKV replication and particle assembly. When the investigation was extended to viruses from various positive and negative RNA viral families, we found that not only phleboviruses rely on GBF1 for infection, but also Flavi-, Corona-, Rhabdo-, and Togaviridae. In contrast, silencing or blocking GBF1 did not abrogate infection by the human adenovirus serotype 5 and immunodeficiency retrovirus type 1, the replication of both requires nuclear steps. Together our results indicate that UUKV relies on GBF1 for viral replication, assembly and egress. This study also highlights the proviral activity of GBF1 in the infection by a broad range of important zoonotic RNA viruses.